THE NEXT CLASS. - Ciccarelli, Maura (Literacy Today (2411-7862))
The article reports on several under-30 achievers who have been contributing towards the goal of literacy for all. The young achievers being discussed here include Deborah Ahenkorah Osei-Agyekum who introduced Golden Baobab Prize (GBP); founder of Ananda Siksha Niketan, Babar Ali; and executive director of League of Young Female Leaders, Hikmat Baba Dua.